2017
DOI: 10.1186/s40781-017-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding garlic leaves on rumen fermentation, methane emission, plasma glucose kinetics, and nitrogen utilization in sheep

Abstract: BackgroundGarlic and its constituents are reported to have been effective in reducing methane emission and also influence glucose metabolism in body; however, studies in ruminants using garlic leaves are scarce. Garlic leaves contain similar compounds as garlic bulbs, but are discarded in field after garlic bulb harvest. We speculate that feeding garlic leaves might show similar effect as garlic constituents in sheep and could be potential animal feed supplement. Thus, we examined the effect of freeze dried ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
5
17
0
3
Order By: Relevance
“…Recent ndings showed that the garlic (for example garlic powder), garlic extracts (for example garlic oil) and garlic by-products (for example garlic husk and garlic leaf) had potential to modify rumen fermentation, improve animal performance, and might be an alternative for growth promoting feed antibiotics [16][17][18]. In the present study, an increase of ADG was observed in the GAS group compared with that in the control group, which is consistent with previous study [18].…”
Section: Discussionsupporting
confidence: 92%
“…Recent ndings showed that the garlic (for example garlic powder), garlic extracts (for example garlic oil) and garlic by-products (for example garlic husk and garlic leaf) had potential to modify rumen fermentation, improve animal performance, and might be an alternative for growth promoting feed antibiotics [16][17][18]. In the present study, an increase of ADG was observed in the GAS group compared with that in the control group, which is consistent with previous study [18].…”
Section: Discussionsupporting
confidence: 92%
“…Bu sorunu çözmek için antibiyotiklere alternatif olabilecek yem katkı maddelerinin geliştirilmesine yönelik çalışmalar artmıştır. Bu çalışmalar sonucu aromatik bitki ve bu bitkilerden izole edilen esansiyel yağların antibiyotiklere alternatif olabilecekleri ortaya konulmuştur (11,14,23,36). Esansiyel yağların çeşitli mikroorganizmalara karşı bakterisit, fungusit ve antiparazitik etkiye sahip oldukları bildirilmektedir (5, 10,11,12,36).…”
Section: Introductionunclassified
“…Bu çalışmalar sonucu aromatik bitki ve bu bitkilerden izole edilen esansiyel yağların antibiyotiklere alternatif olabilecekleri ortaya konulmuştur (11,14,23,36). Esansiyel yağların çeşitli mikroorganizmalara karşı bakterisit, fungusit ve antiparazitik etkiye sahip oldukları bildirilmektedir (5, 10,11,12,36). Bu yağların antimikrobiyal mekanizmaları henüz tam olarak aydınlatılmamasına rağmen, mikrooganizmaların hücre zarı lipid (lipofilik) tabakasının (3), kimyasal yapısı (5, 13) ile hücre duvarı enzimlerini olumsuz etkileyerek yapılarını bozdukları ve gelişmelerini sınırlamak suretiyle etki yaptıkları bildirilmektedir (4, 5).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Chu et al [9] reported an improvement in meat quality and economic income when garlic stalk silage was fed to steers during the fattening period. More recently, Panthee et al [11] reported that inclusion of garlic leaves at 2.5 g/(kg BW 0.75 ·d) had no negative effects on ruminal fermentation characteristics and had positive N utilization in sheep. These studies investigated the feed value of garlic stalk silage for beef cattle, or the bioactive components in garlic stem and leaf silage for sheep.…”
Section: Introductionmentioning
confidence: 99%